Improvements in Attention Following Cognitive Training With the Novel “Decoder” Game on an iPad - Savulich, George; Thorp, Emily; Piercy, Thomas; Peterson, Katie A.; Pickard, John D.; Sahakian, Barbara J. (Frontiers in Behavioral Neuroscience, 2019)
Work and study increasingly rely on the use of technologies requiring individuals to switch attention rapidly between emails, texts and tasks. This has led to healthy people having problems of attention and concentration and difficulties getting into the ‘flow,’ which impedes goal attainment and task completion. Possibly related to this, there is an increasing diagnosis of attention deficit hyperactivity disorder (ADHD) and prescriptions of drugs such as methylphenidate. In addition to ADHD, attention is impaired in other neuropsychiatric disorders, such as schizophrenia and in traumatic brain injury. Based on neuropsychological and neuroimaging evidence, we developed ‘Decoder’, a novel game for targeted cognitive training of visual sustained attention on an iPad. We aimed to investigate the effects of cognitive training in 75 healthy young adults randomly assigned to a Cognitive Training (eight hours of playing Decoder over four weeks; n = 25), Active Control (eight hours playing Bingo over four weeks; n = 25) or Passive Control (continuation of activities of daily living; n = 25) group. Results indicated that cognitive training with Decoder was superior to both control groups in terms of increased target sensitivity (A’) on the CANTAB Rapid Visual Information Processing (RVP) test, indicating significantly improved sustained visual attention. Individuals playing Decoder also showed significantly better performance on the Trail Making Test compared with those playing Bingo. Significant differences in visual analogue scales were also found between the two gaming groups, such that Decoder received higher ratings of enjoyment, task-related motivation and alertness across all hours of game play. These data suggest that cognitive training with Decoder is an effective non-pharmacological method for enhancing attention in healthy young adults, which could be extended to clinical populations in which attentional problems persist.